The link between gender dysphoria and autism spectrum disorder: a review - Ana Rita de Albuquerque Rodrigues (2021)
Recently, there has been an increased interest in the potential link between autism spectrum disorder and gender dysphoria, and this narrative review proposes exploring further on this subject. The existing literature has been somehow equivocal and limited concerning this issue. Nevertheless, recent evidence has pointed to a tendency for the co-occurrence of these two conditions. In fact, a diversity of papers has found an augmented prevalence of autism spectrum disorder in gender dysphoric populations (especially in studies of children and adolescents), which suggests that autism spectrum disorder in people with gender dysphoria is more prevalent than in the general population. Additionally, gender dysphoria is overrepresented in the autistic population in comparison to the general population. Contributing factors interplaying in the co-occurrence between autism spectrum disorder and gender dysphoria most probably include biological, psychological and social components. There is still a long way towards the understating of the relation between these two conditions and specific data about Portugal is lacking. Nonetheless, taking in consideration the impact of this relation in the diagnosis and treatment of these individuals, it urges to motivate researchers and clinicians to explore further the putative link between autism spectrum disorder and gender dysphoria. Thus, more robust data, based in longitudinal population studies and with larger samples, is needed, in order to provide the optimal care to these patients.